Uniformity Trials for Determination of Optimum Size and Shape of Plots/Blocks for Experimentation with Acacia catechu - Agnihotri, Y.; Agarwal, M. C. (Indian Forester, 1995)
An uniformity trial for determination of optimum size and shape of plots and blocks was conducted on 8 years old plants of Acacia catechu (spacing 2m Ã— 2m) at the Central Soil and Water Conservation Research and Training Institute, Research Centre, Chandigarh. Height and GBH data of all the individual plants were recorded in 24 Ã— 24 compartment and analysed for determination of optimum plot and block sizes for conducting field experiments. A plot of size 8-12 plants appears to be optimum. Smith equations fitted well in the CV and plot size data and indicated the neighboring plots to be uncorrelated. For a fixed size of plot, its shape did not indicate any consistent effect on CV. In general, blocks were found to be more efficient than without blocking arrangement.